From Aspiration to Obligation: A Contractual Sustainability Framework for the Egyptian Construction Industry - Ali, Salma (AUC Knowledge Fountain, 2026)
The construction industry is responsible for approximately 40% of global energy consumption and 35% of total waste generation, making it one of the most significant contributors to the global sustainability challenge. In Egypt, that challenge takes a specific contractual form. Egypt’s construction sector contributes approximately 23% of national energy consumption, yet the survey findings reveal that 63.5% of construction professionals report that sustainability clauses rarely or never appear in contracts, and only 11.5% confirm the presence of enforceable provisions with measurable targets. This gap is structural rather than attitudinal. Competitive procurement penalises voluntary sustainability investment, and without contractual obligation, awareness does not translate into action. This study develops and validates a contract-ready sustainability performance framework for the Egyptian construction context. The research employs a sequential mixed-methods design combining a systematic literature review, a survey of 52 industry professionals, and semi-structured interviews with six senior experts. Multi-Criteria Decision Analysis evaluates 20 candidate sustainability practices against five weighted criteria: importance (30%), feasibility (25%), measurability (20%), enforceability (15%), and stakeholder priority (10%). A hybrid Relative Importance Index and Analytic Hierarchy Process approach resolves the compressed RII range of 0.111, with expert judgements confirming acceptable consistency at CR = 0.08. Sensitivity analysis confirms that 10 of 11 clauses retain their tier assignments across all five alternative weighting scenarios. Statistically significant importance–implementation gaps emerge across all assessed practices at p < .001, and weak correlations of r = 0.18 to 0.34 confirm that professional recognition of sustainability value does not predict compliance behaviour. The validated framework consolidates these findings into eleven contractual articles with tiered weighting. Worker safety, community engagement, and energy efficiency carry Tier 1 Critical status at 15% each. The framework deploys binary clause scoring: each clause scores 100 if the minimum performance target is met and 0 if it is not. A contractor achieves the Overall Excellence Bonus when the weighted average across all clauses reaches or exceeds 90% for nine or more consecutive months. Enforcement operates through a four-tier graduated mechanism ranging from written warning to payment withholding of 1 to 5% and, in extreme cases, contract termination. Performance bonuses reach a maximum of 3% of contract value. More Importantly, 80.8% of respondents expressed a preference for mandatory contractual requirements, confirming that practitioners themselves recognise the collective action problem that voluntary approaches cannot resolve. The framework applies to FIDIC-based contracts but its eleven-article modular structure can be incorporated into any standard form contract. The contribution is both theoretical and practical. Theoretically, it advances scholarship on contractual governance by addressing collective action challenges in competitive procurement environments. In practice, it offers a framework that can be directly applied within Egyptian public and private-sector procurement systems.